ANALISIS PENGARUH PAJAK DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN MINAHASA - Frangky Martinus Mea; Vicky V. J. Panelewen; Arie D. P. Mirah (Sam Ratulangi University, 2017)
This study aims to analyze the effect of Local Tax on Local Revenue in Minahasa District Year 2011-2015. This research was conducted from January to March 2017 in Minahasa District, North Minahasa District and Tomohon City with the object of Local Taxes research from 2011 to 2015. This study uses secondary data obtained from Minahasa District Revenue Office, Regional Finance Board and Asset Manager of Minahasa District, North Minahasa District and Tomohon City and Statistics Agency of Minahasa District. Data analysis used Contribution and Growth Matrix Analysis and Time Series Analysis. This study found that the contribution of local taxes to the original income of the period of 2011-2015 is still below 50 percetn and the local revenue is at the 5 percent level of Central Government Fund Transfer Income to the regions. This has resulted in poor welfare and prosperity of the population reflected in the per capita income level that is still lacking and the level of regional independence is still low. Analysis of regional tax trends for the year 2016-2020 has increased but still below 5 (five) billion rupiah each year so it still needs to be improved.